Transformation of Neurospora crassa with the cloned am (glutamate dehydrogenase) gene. - Kinsey, J A (1984)
We used DNA containing the am gene of Neurospora crassa, cloned in the lambda replacement vector lambdaL-47 (this clone is designated lambdaC-10), and plasmid vector subclones of this DNA to transform am deletion and point mutant strains. By means of subcloning, all sequences required for transformation to am prototrophy and expression of glutamate dehydrogenase have been shown to reside on a 2.5-kilobase BamHI fragment. We also characterized several am+ strains that were obtained after transformation with lambdaC-10. These strains showed Mendelian segregation of the am+ gene, although less than 50% of the transformed strains showed the normal linkage relationship of am with inl. In all cases tested, the strains had incorporated lambda DNA as well. The lambda DNA also showed a Mendelian segregation pattern. In one case, the incorporation of am DNA in a novel position was associated with a mutagenic event producing a strain with a very tight colonial morphology. In all cases in which the am+ gene had become the resident of a new chromosome, glutamate dehydrogenase was produced to only 10 to 20% of the wild-type levels.